Performance prediction and performance-based task allocation - Trautmann, Stefan T.; Vollmann, Martin; Becker, Christoph (Journal of economic behavior & organization, 2024)
Self-perception and perception by others can diverge. Such differences can play an important role in corporate governance settings, for example in the context of task allocation. We run two experiments to study how predictions about own performance and the performance of others develop over time and how they influence allocation in performance-based decisions. Our findings indicate that people underestimate their own performance, but are too keen to take up performance-dependent tasks. Observers form accurate performance estimates about the performer based on observation. However, when making allocation decisions on the basis of the performer's self-assessment only, they are too hesitant to trust in the performer's success.